Phenotypes in Brugada syndrome with different genotypes triggered by fever or inflammation using gene-edited iPSCs - Li, Yingrui; Rose, Lena; Prädel, Timo; Kleinsorge, Mandy; Fan, Xuehui; Meng, Zenghui; Yan, Chen; Liu, Rui; Lei, Xinhao; Zhao, Binyi; Yang, Guoqiang; Liao, Zhenxing; et al. (Stem cell research & therapy, 2025)
Fever or inflammation state may enhance the Brugada syndrome (BrS) phenotype in some but not all patients. However, the underlying mechanism in human cardiomyocytes has not yet been clarified.
Gesehen am 22.01.2026